Should pensions be progressive? Yes, at least in Germany! - Hans Fehr; Manuel Kallweit; Fabian Kindermann (Center for Economic Studies and ifo Institute (CESifo), 2011)
Recent reforms that aim at reducing the upcoming burdens of population ageing might seriously harm low income individuals. An increase in old-age poverty and disability will be the result. Under this prospect, the present paper quantitatively characterizes the optimal progressivity of unfunded pension systems in an overlapping generations model with idiosyncratic income, disability and longevity risk as well as endogenous labor supply at the intensive and extensive margin. Focusing on the German pension system, our model features the most recent demographic projections and distinguishes three skill classes with skill-dependent risk profiles. Starting from a baseline path that reflects a purely earnings related pension system, we increase the degree of progressivity and compute the resulting macroeconomic, welfare and efficiency effects. For our most preferred parametrization we find an optimal flat-rate pension share of 40 percent. This indicates that in Germany recent reforms that aim at raising retirement age and cutting benefit levels should be complemented by increases in pension progressivity, since improved insurance provision dominates higher labor supply distortions. In addition, we also find that reductions in the benefit level (i.e. privatization) will only reduce economic efficiency.
Keywords: C68; H55; J11; J26; 330; stochastic OLG model; tax-benefit linkage; endogenous retirement; population ageing